2011
DOI: 10.1016/j.jtcvs.2010.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of mediastinal lymph node sampling versus complete lymphadenectomy during pulmonary resection in the patient with N0 or N1 (less than hilar) non–small cell carcinoma: Results of the American College of Surgery Oncology Group Z0030 Trial

Abstract: Objective To determine if mediastinal lymph node dissection (MLND) improves survival compared to mediastinal lymph node sampling (MLNS) in patients undergoing resection for N0 or non-hilar N1, T1 or T2 non-small cell lung cancer (NSCLC). Methods Patients with NSCLC underwent sampling of 2R, 4R, 7 and 10R for right sided tumors, and 5, 6, 7 and 10L for left sided tumors. If all were negative for malignancy, patients were randomized to no further lymph node sampling (MLNS) or complete MLND. Results Of 1,111 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
390
2
12

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 641 publications
(416 citation statements)
references
References 14 publications
12
390
2
12
Order By: Relevance
“…It is important to keep in mind that no benefit has been demonstrated with routine lymphadenectomy in early stage NSCLC (ACOSOG Z0030) [7]. Thus, we perform TEMLA in situations with a high likelihood of occult N2 disease and for restaging the mediastinum after neoadjuvant therapy; in the latter situation, other modalities of restaging such as PET/CT and EBUS are not very accurate.…”
Section: Initial Resultsmentioning
confidence: 99%
“…It is important to keep in mind that no benefit has been demonstrated with routine lymphadenectomy in early stage NSCLC (ACOSOG Z0030) [7]. Thus, we perform TEMLA in situations with a high likelihood of occult N2 disease and for restaging the mediastinum after neoadjuvant therapy; in the latter situation, other modalities of restaging such as PET/CT and EBUS are not very accurate.…”
Section: Initial Resultsmentioning
confidence: 99%
“…Nowadays, the standard surgical treatment of early-stage NSCLC is lobectomy with systematic lymph node dissection (LND) as recommended by the guidelines (3,4), which capable of providing accurate staging (5,6), detecting occult metastasis (7) and improving survival (5,8,9). However, randomized trials have not demonstrated that LND has more survival benefit than sampling (7,10). Since advanced radiographic techniques become available and regular medical examination grows popular, early-stage NSCLC patients have occupied a larger proportion.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of lymph node removal (dissection versus sampling) and its impact on survival has been addressed by several randomized trials (2,3). The biggest randomized trial Z0030 demonstrated that mediastinal lymph node dissection did not improve survival in patients with early stage non-small…”
Section: Introductionmentioning
confidence: 99%